Why Plato could not simply embrace Democracy? Misology and Democracy in Plato’s Thought (Revista Archai, 2024)
This paper aims to look at the ancient city of Athens and some of its political challenges through the eyes of Plato. I will do this by relating two concepts that permeate Plato's political concerns: democracy and misology. Beyond the tragic event of Socrates' death at democratic hands, there is perhaps something even deeper in Plato's struggle to see democracy as something that can work, so to speak. Plato no doubt has a profoundly pessimistic view of the human being. And the city, who was traditionally supposed to educate men, is not delivering anymore (if ever). First of all, Plato clearly identifies the origin of political and social instability in the economic imbalance between πλοῦτος (richness) and πενία (poverty). Secondly, Plato's diagnosis, what his eyes are seeing, is even more perceptive and accurate. He outlines a second source of problem for democracy, one the probably resonate even more dramatically in our very present days: one that Socrates calls misology in the Phaedo: the hatred of discourses. Apart from the fact that there is a significant distance and a radical difference between the democracy of the 5th and 4th centuries, when Plato actually writes his dialogues, the most relevant question that emerges from the investigation is probably that a democracy itself is not something stable, an ontological object, not even today. And Plato was well aware of all this.